Brain diffusion tensor imaging in dogs with degenerative myelopathy. (19th August 2021) - Lewis, Melissa J.; Shomper, Jeremy L.; Williamson, Baye G.; Vansteenkiste, Daniella P.; Bibi, Katherine F.; Lim, Stefanie H. Y.; Kowal, Joseph B.; Coates, Joan R.
Abstract: Background: Degenerative myelopathy (DM) in dogs shares similarities with superoxide dismutase 1‐associated human amyotrophic lateral sclerosis (ALS). Brain microstructural lesions are quantified using diffusion tensor imaging (DTI) in ALS patients. Objective: Characterize brain neurodegenerative changes in DM‐affected dogs using DTI. Animals: Sixteen DM‐affected and 8 control dogs. Methods: Prospective observational study. Brain DTI was performed at baseline and every 3 months on DM‐affected dogs and compared to controls. Fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity were calculated on specified regions of interest. Gait scores (0, normal to 14, tetraplegia) were assigned at each scan. Diffusion tensor imaging values in DM‐affected dogs were compared to controls, gait scores, and evaluated over time. Results: Mean age was 5.7 years (SD 3.2) in controls and 9.7 years (SD 1.4) in DM‐affected dogs. In DM‐affected dogs, mean baseline gait score was 4 (SD 1), and mean score change from baseline to last scan was 4.82 (SD 2.67). Nine dogs had ≤3 scans; 7 had >3 scans. Accounting for age, no differences in DTI indices were identified for any brain or proximal spinal cord regions between DM‐affected dogs and controls ( P  > .05). Diffusion tensor imaging values poorly correlated with gait scores ( R 2  < .2). No significant changes were identified in diffusion indices over time ( P  > .05). Conclusions and Clinical Importance: Diffusion tensor imaging indices did not differentiate DM‐affected from control dogs, detect longitudinal changes, or differentiate disease severity. Findings do not yet support brain DTI as an imaging biomarker.